Predictors of workplace deviant behaviour : HRD agenda for Malaysian support personnel. - Alias, Mazni; Mohd Rasdi, Roziah; Ismail, Maimunah; Abu Samah, Bahaman (Emerald Group Publishing Limited, 2013)
The purpose of this paper is to develop a theoretical model of the determinants of workplace deviant behaviour among support personnel in Malaysian Public Service organisations. Design/methodology/approach: This study is based on reviews of past studies on workplace deviant behaviour. To conduct the literature review, several keywords were identified. Several electronic databases available at the university's library such as Springer, Proquest, SAGE, Emerald, EBSCOHost, Science Direct, and Blackwell Synergy were used to search for supporting materials and resources. Findings: In the reviews, the authors found three potential groups of workplace deviant behaviour determinants among support personnel. The determinants are individual-related factors, organisational-related factors, and work-related factors. The paper established job satisfaction as a mediating variable between the three potential groups of determinants and workplace deviant behaviour. Practical implications: Future research could provide a more definitive theoretical statement of workplace deviant behaviour and develop an additional proposition which may be derived from a more refined theory. Practical interventions for HRD professionals were suggested to assist individuals and organisations towards reducing the prevalence of workplace deviant behaviour. Originality/value: The research yields a theoretical framework that outlines the predictive potential of the three key factors in explaining workplace deviant behaviour among support personnel. The factors can be considered in developing HRD practices.